A well fabricated PtSn/SiO2 catalyst with enhanced synergy between Pt and Sn for acetic acid hydrogenation to ethanol. Issue 56 (24th May 2016) - Xu, Guozhen; Zhang, Jian; Wang, Shengping; Zhao, Yujun; Ma, Xinbin
Abstract : PtSn/SiO2 -MTSG catalyst prepared by MTSG method shows excellent hydrogenation activity due to the enhanced synergy between Pt and Sn species. Abstract : This work reported a well-fabricated PtSn/SiO2 catalyst prepared by a modified two-step sol–gel (MTSG) method. The adoption of strong electrostatic adsorption (SEA) and sol–gel (SG) method could give both a significantly high Pt dispersion and a large amount of Lewis acid sites. The homogenous distribution of Sn species could not only provide more opportunity for the Pt precursor to disperse on the support by forming Pt–(O–Sn) y 2− y analogous species, but also enhance the synergy between Pt and Sn species. Consequently, an excellent activity was achieved in the hydrogenation of acetic acid (AcOH) with a conversion of 100% and ethanol (EtOH) selectivity of 93%. Investigations on the effect of Sn/Pt molar ratio showed that the dispersion of Pt decreases obviously with the increasing Sn/Pt ratio due to the geometric or electronic effects caused by SnO x species. A balancing effect between Pt active sites and Lewis acid sites was found to be responsible for the superior catalytic performance in AcOH hydrogenation. Moreover, a parallel reaction path model was proposed for the hydrogenation of AcOH over PtSn/SiO2 catalyst, in which ethanol and ethyl acetate (AcOEt) are formed competitively through the adsorbed ethoxy intermediate.